Theocracy and Resilience Against Economic Sanctions - Alireza Naghavi; Giuseppe Pignataro (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper provides a simply theory to explain the impact of sanctions on a regime's policies and behavior. Sanctions are generally put to strip the target country from its available rents and weaken the government's stance against growing discontent in the population. We show however that sanctions may give legitimacy to an incumbent government by influencing the optimal level of religious ideology provided by the state and further stabilizing its grip to power and rents. While in a good state of nature sanctions build resilience as long as religious ideology among the population is strong, at bad times they compel the target country to move towards ideological moderation. In a world of asymmetric information, the target country always finds it optimal to send an accurate signal in order to successfully convince the imposing side to lift sanctions and reach a win-win outcome.
Keywords: H10; Z12; P48; D74; D83; 330